Ice templated nanocomposites containing rod-like hematite particles: Interplay between particle anisotropy and particle-matrix interactions - Kumaraswamy, Guruswamy; Suresh, Karthika; Lama, Hisay; Basavaraj, Madivala G.; Satapathy, Dillip K. (Journal of Applied Physics, 2020)
We demonstrate that the mechanical response of ice templated nanocomposite scaffolds prepared from ellipsoidal hematite particles is determined by both the particle aspect ratio and the interaction between the particles and the matrix polymer. We ice template aqueous dispersions of hematite particles, polyethyleneimine, and diepoxy crosslinker and crosslink the polymer in the frozen state. This protocol results in the formation of elastic macroporous monoliths capable of complete recovery from large compressive strains. Hematite particles show an inversion of their surface charge with pH: they are negatively charged at a basic pH and positively charged under acidic conditions. This allows us to change the interaction between hematite particles and crosslinked matrix polymer that they are embedded in, simply by immersing the monoliths in aqueous solutions with different pH's. We report that under basic conditions, viz, when polyethyleneimine adsorbs on the particle surface, there is a decrease in the monolith modulus with an increase in the particle aspect ratio. We demonstrate that this correlates with a change in the mechanism of monolith response: from wall compression for isotropic particles to wall bending for anisotropic particles with an aspect ratio of 4. Under acidic conditions (pH=2), where hematite particles show a positive zeta potential, the monolith modulus increases with the aspect ratio of the ellipsoidal fillers. Understanding the interplay between filler aspect ratio and filler-matrix interaction has important implications for the control of nanocomposite mechanical properties.